A astucia de Aquiles no canto I da Ilíada (Argos, 2025)
This article develops an interpretation of Iliad I.131-32, showing mainly by an analysis of the verses that precede this passage the reasons of Agamemnon's reaction to Achilles' action in the αγορή. As a result we will distinguish traces of cunning (μητις) in Achilles' words.
Keywords: epos; Homer; Iliad; Achilles; cunning